Una propuesta de análisis textual a partir de los postulados del Análisis Crítico del Discurso - Murillo Medrano, Jorge (2004)
This work presents the Model of Textual Analysis provided by the Critical Analysis of the Speech. Its heoretical and methodological principIes are described so that they can be thereafter applied to a text dealing with the theme of transparence. The aim is to attract the social science investigators' interest toward this Model of Textual Analysis.